Synthesis and crystal structure of [HexNH3]2[HC2O4]2·H2O: A novel hydrogen oxalate hydrate organic salt showing antimicrobial activity against Streptomyces - Ba, Mamadou; Diallo, Waly; Sarr, Alhousseynou; Traore, Bocar; Ndoye, Daouda; Mbaye, Nalla; Sidibe, Mamadou; Plasseraud, Laurent; Cattey, Helene (European Journal of Chemistry, 2025)
The new monohydrated n-hexylammonium hydrogen oxalate salt [HexNH3]2[HC2O4]2·H2O (1) (HexNH3 = C6H16N+) has been prepared at room temperature, by mixing dehydrated oxalic acid with n-hexylamine. Salt 1 isolated as single-crystals, crystallizes in the orthorhombic system (space group Pna21) with cell constants of a = 14.1534(8) Å, b = 5.6656(3) Å, c = 26.8153(16) Å, V = 2150.3(2) Å3 and Z = 4. Two n-hexylammonium cations, two hydrogen oxalate anions, and one water molecule compose the asymmetric unit. All components of salt 1 are linked through N-H···O and O-H···O hydrogen bonding interactions leading to an extended supramolecular self-assembly. Structural characterization of 1 was completed by infrared and UV-visible spectroscopy. Elemental analysis (C, H, and N) also corroborates the X-ray crystal structure. The antibacterial activity of salt 1 against a bacterial species of the genus Streptomyces, extracted from potatoes, was then investigated. The antibiotic susceptibility test revealed that the bacteria were highly sensitive to salt, from a concentration of 6 mg/mL, thus acting as an effective bactericide.